The kdr-bearing haplotype and susceptibility to Plasmodium falciparum in Anopheles gambiae: genetic correlation and functional testing. (December 2015) - Mitri, Christian; Markianos, Kyriacos; Guelbeogo, Wamdaogo; Bischoff, Emmanuel; Gneme, Awa; Eiglmeier, Karin; Holm, Inge; Sagnon, N'Fale; Vernick, Kenneth; Riehle, Michelle
Abstract Background Members of theAnopheles gambiae species complex are primary vectors of human malaria in Africa. It is known that a large haplotype shared betweenAn. gambiae andAnopheles coluzzii by introgression carries point mutations of the voltage-gated sodium channel genepara, including the L1014Fkdr mutation associated with insensitivity to pyrethroid insecticides. Carriage of L1014Fkdr is also correlated with higher susceptibility to infection withPlasmodium falciparum . However, the genetic mechanism and causative gene(s) underlying the parasite susceptibility phenotype are not known. Methods Mosquitoes from the wild Burkina Faso population were challenged by feeding on naturalP. falciparum gametocytes. Oocyst infection phenotypes were determined and were tested for association with SNP genotypes. Candidate genes in the detected locus were prioritized and RNAi-mediated gene silencing was used to functionally test for gene effects onP. falciparum susceptibility. Results A genetic locus, Pfin6, was identified that influences infection levels ofP. falciparum in mosquitoes. The locus segregates as a ~3 Mb haplotype carrying 65 predicted genes including thepara gene. The haplotype carrying thekdr allele ofpara is linked to increased parasite infection prevalence, but many single nucleotide polymorphisms on the haplotype are also equally linked to the infection phenotype. Candidate genes in the haplotype were prioritized and functionally tested. Silencing ofpara did not influenceP. falciparum infection, while silencing of a predicted immune gene, serine proteaseClipC9, allowed development of significantly increased parasite numbers. Conclusions Genetic variation influencingPlasmodium infection in wildAnopheles is linked to a natural ~3 megabase haplotype on chromosome 2L that carries thekdr allele of thepara gene. Evidence suggests thatpara gene function does not directly influence parasite susceptibility, and the association ofkdr with infection may be due to tight linkage ofkdr with other gene(s) on the haplotype. Further work will be required to determine if ClipC9 influences the outcome ofP. falciparum infection in nature, as well as to confirm the absence of a direct influence bypara .